Cornplexation of Cm(III) with blood serum proteins: recombinant human serum albumin (rHSA) - Adam, Nicole; Reitz, Cedric Y.; Ditter, Anna-Lena; Panak, Petra (Radiochimica acta, 2021)
The complexation of Cm(III) with the recombinant human serum albumin (rHSA) (characterized by single deletion of residue Asp-1), is studied in dependence of pH and rHSA concentration using time-resolved laser fluorescence spectroscopy (TRLFS). A Cm(III) rHSA species is formed between pH 6.4 and 10.0 with the conditional stability constant being logK = 6.47 at pH = 7.4. Competition titration experiments with Cu(II) and Zn(II) confirm complexation at the N-terminal binding site (NTS) of rHSA and exclude the involvement of the Multi-Metal Binding Site (MBS). Comparison with a previous study on Cm(III) interaction with native albumin, HSA, points out, that residue Asp-1 is involved in Cm(III) binding to HSA but is not crucial for Cm(III) complexation at the NTS. The results are of major importance for a better understanding of fundamental actinide-protein interaction mechanisms which are highly required for the identification and characterization of relevant distribution pathways of incorporated radionuclides.
Gesehen am 10.08.2021